Bentuk dan Fungsi Tulisan Tato Arab di Media Sosial - Abdul Jawat Nur (Institut Agama Islam Negeri (IAIN) Metro, 2019)
This paper will describe the form of lingual units and the function of writing on Arabic tattoos on social media. The phenomenon of Arabic tattoo writing is interesting to study because based on the data found, it is known that there are various types of Arabic tattoo writing, such as words, phrases, and sentences. In addition, it was also found the function of Arabic tattoo writing on social media, including the form of self-expression or group expression. This research was carried out through three strategic stages, namely: the stage of data provision, data analysis, and presentation of the results of data analysis. Based on the research that has been done, it is concluded that on social media found Arabic tattoo writing in the form of words, phrases, and sentences. When viewed from the function of the language, Arabic tattoo writing has the functions of (1) fatigue, (2) referential, and (3) imaginative.